STUDY OF LIPID PROFILE IN NEPHROTIC SYNDROME BEFORE AND AFTER REMISSION IN CHILDREN IN A TERTIARY CARE HOSPITAL IN A SUB URBAN POPULATION (Journal of Pharmaceutical Negative Results, 2022)
Background: Nephrotic syndrome, is defined by the presence of nephrotic-range proteinuria, edema, hyperlipidemia, and hypoalbuminemia.1 Our study aims to determine the proportion of various lipid fractions elevated inNephroticsyndromeandanalyseswhetherthereispersistentHyperlipidemiaafterRemission. Aims: To assess the lipid profile in nephrotic syndrome before and after remission in children in a tertiary care hospital in a sub urban population. Materials and Methods: Thestudy included 65 newly diagnosed nephrotic syndrome in pediatric ward . Otherrelevantinvestigationsweredone, lab investigations were done in all patients. SPSS 24was used for statistical analysis of results Conclusion: Hyperlipidaemia was found to behigher in Frequent relapser/ steroid dependent patients than steroid responsiveboth during disease and Remission. Degree of hyperlipidemia is related to duration of treatment and relapse .SO regular follow up is necessary in all nephrotic patients, for better prognosis .